2017
DOI: 10.1111/bdi.12482
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic patterns of lithium poisoning: a study of the effect/concentration relationships in the rat

Abstract: The severity of lithium-induced encephalopathy is dependent on the poisoning pattern, which was previously shown to determine lithium accumulation in the brain. Our data support the proposition that electroencephalography is a sensitive tool for scoring lithium-related neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…We may also have used insufficient doses or duration of exposure in our prolonged lithium treatment regimens to induce lithium‐related brain injuries. However, our findings were consistent with our previous observations of reversible hypolocomotion and electroencephalography‐based encephalopathy in the three lithium‐poisoning patterns 9,10 . Additionally, neuroprotective rather than neurotoxic effects have been reported extensively in animals receiving lithium at pharmacological doses, 16 thus supporting our findings.…”
Section: Discussion/conclusionsupporting
confidence: 93%
See 2 more Smart Citations
“…We may also have used insufficient doses or duration of exposure in our prolonged lithium treatment regimens to induce lithium‐related brain injuries. However, our findings were consistent with our previous observations of reversible hypolocomotion and electroencephalography‐based encephalopathy in the three lithium‐poisoning patterns 9,10 . Additionally, neuroprotective rather than neurotoxic effects have been reported extensively in animals receiving lithium at pharmacological doses, 16 thus supporting our findings.…”
Section: Discussion/conclusionsupporting
confidence: 93%
“…Lithium dose regimens used in this study were similar to those used in our previous works, which characterized lithium kinetics in the plasma, erythrocytes, cerebrospinal fluid and brain and described the time course and extent of reversible lithium‐induced neurotoxicity (i.e., electroencephalography‐graded encephalopathy and impairment of locomotion activity and anxiety‐like behaviour) 7,9,10 . All our previous findings showed that the dose regimens used in the rat adequately mimicked the three patterns of lithium poisonings observed in humans 2 .…”
Section: Discussion/conclusionsupporting
confidence: 69%
See 1 more Smart Citation
“…The exact mechanisms involved in lithium‐induced neurotoxicity remain unknown. Recent rat studies mimicking acute and acute‐on‐chronic lithium poisoning have shown that lithium‐induced neurotoxicity was associated with lithium accumulation in the brain followed by slower and delayed elimination in comparison to the blood . If pharmacokinetic studies have demonstrated the effectiveness of ECTR in removing lithium from the blood, there is no evidence that ECTR could enhance lithium elimination from the brain .…”
Section: Discussionmentioning
confidence: 99%
“…Recent rat studies mimicking acute and acute-on-chronic lithium poisoning have shown that lithium-induced neurotoxicity was associated with lithium accumulation in the brain followed by slower and delayed elimination in comparison to the blood. [14][15][16] If pharmacokinetic studies have demonstrated the effectiveness of ECTR in removing lithium from the blood, 17,18 there is no evidence that ECTR could enhance lithium elimination from the brain. 1,3 In accordance, no difference in outcome was reported between lithium-poisoned patients for whom haemodialysis was carried out and those for whom it was recommended by the poison control centre but not done, suggesting that indications for haemodialysis in lithium poisoning should be reconsidered to include only the more severe cases.…”
Section: Potential Impact Of Extrip Vs Paris Criteria On the Outcommentioning
confidence: 99%